ANALYSIS OF EATING BEHAVIOR IN CONSTIPATION WITH LAWRENCE GREEN THEORY APPROACH - Wiwit Dwi Nurbadriyah (Jurnal Kesehatan Mesencephalon, 2022)
Abstract:Constipation is an obstruction of defecation from normal habits where there is infrequent defecation, the amount of stool is less, the consistency is hard and dry. One of the factors that cause constipation is the lack of knowledge and attitudes in carrying out dietary behavior and the lack of support from the family. The purpose of this study was to analyze dietary behavior in the incidence of constipation. The design of this research is Analytical Observation with Cross Sectional approach. Samples were taken using the purposive sampling technique in accordance with the inclusion and exclusion criteria of dietary behavior at MTs Al-Hidayah, Wajak Village, Wajak District, Malang Regency, with a total of 114 respondents. Collecting data in this study using a questionnaire sheet. The statistical test used is linear regression analysis test. The results showed that there was an influence between knowledge and p-value results of 0.007 < (0.05) with a coefficient of 0.673, attitude p-value